Characterization of the terpenoids composition of beers made with the French hop varieties: Strisselspalt, Aramis, Triskel and Bouclier. - Hop Special - Steyer, Damien; Clayeux, Céline; Laugel, Bernadette (BrewingScience, 2013)
Among the various compounds brought in to beer by hop, mono- and sesqui- terpenoids are the most studied and contribute to a certain extent to the hoppy aroma of beer. Previous studies have indicated that the concentration of these compounds in beer depends on the hop variety. The impact of new hop varieties created by the French hop growers association and their cooperative in comparison to the old variety Strisselspalt on the terpenoid content in beer has been analyzed by Stir-Bar Sorptive-Extraction-Gas-Chromatography (SBSE-GC-MS). Our results reveal that the new variety Aramis has a similar terpenoid profile to the Strisselspalt variety, both showing a similar content of sesquiterpenoids. In comparison, the new variety Bouclier was rather low in sesquiterpenoid content whereas Triskel showed the highest concentration of monoterpenoids, especially linalool.